Penerapan Materi PAI dalam Projek Penguatan Profil Pelajar Pancasila Melalui Batik Ecoprint di Sekolah Dasar - Khalifah, Tatik; Ikhsan Ghofur, Muhammad (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research explores the integration of Islamic Religious Education (PAI) in the Project to Strengthen the Pancasila Student Profile through Batik Ecoprint. The study examines how the values of Pancasila and Islamic teachings can be combined to foster students' character development, creativity, and environmental awareness. The Batik Ecoprint project serves as an innovative educational approach that not only introduces students to traditional arts but also aligns with ecological consciousness and moral values emphasized in PAI. This qualitative research employs a case study method to analyze the project's implementation, highlighting its effectiveness in promoting religious values, cultural preservation, and environmental sustainability. The findings indicate that the integration of PAI with local cultural elements, such as Batik Ecoprint, contributes to shaping well-rounded students who embody the Pancasila profile with a strong foundation in religious principles